Molecular genetic basis of allelic polymorphism in malate dehydrogenase (mdh) in natural populations of Escherichia coli and Salmonella enterica. - Boyd, E F (1994)
Nucleotide sequences of the mdh gene encoding the metabolic enzyme malate dehydrogenase (MDH) were determined for 44 strains representing the major lineages of Escherichia coli and the eight subspecies of Salmonella enterica. Sequence diversity was four times greater in S. enterica than in E. coli, and in both species the rate of amino acid substitution was lower in the NAD(+)-binding domain than in the catalytic domain. Divergence of the mdh genes of the two species apparently has not involved excess nonsynonymous substitutions resulting from the fixation of adaptive amino acid mutations. Allozyme analysis detected 57% of the distinctive amino acid sequences. Statistical tests of the distribution of polymorphic synonymous nucleotide sites identified four possible intragenic recombination events, one involving a single allele of E. coli and three involving alleles of the three subspecies of S. enterica. But recombination at mdh has not occurred with sufficient frequency to obscure the phylogenetic relationships among strains indicated by multilocus enzyme electrophoresis, total DNA hybridization, and sequence analysis of the gapA and putP genes. These findings provide further evidence that the effective (realized) rates of horizontal transfer and recombination for metabolic enzyme and other housekeeping genes are generally low in these species, in contrast to those for loci encoding or mediating the structure of cell-surface and other macromolecules for which recombinants may be subject to strong balancing, directional, or diversifying selection.